Long term cardiovascular impacts after burn and non-burn trauma: A comparative population-based study - Duke, J.; Randall, Sean; Fear, M.; O'Halloran, E.; Boyd, James; Rea, S.; Wood, F. (Pergamon Press, 2017)
© 2017 Elsevier Ltd and ISBI. Objective: To compare post-injury cardiovascular disease (CVD) hospital admissions experienced by burn patients with non-burn trauma patients and people with no record of injury, adjusting for socio-demographic, health and injury factors. Methods: Linked hospital and death data were analysed for a cohort of burn patients (n = 30,997) hospitalised in Western Australia during the period 1980-2012 and age and gender frequency matched comparison cohorts (non-burn trauma: n = 28,647; non-injured: n = 123,399). The number and length of hospital stay for CVD admissions were used as outcome measures. Multivariate negative binomial regression was used to derive adjusted incidence rate ratios (IRR) and 95% confidence intervals (95%CI). Multivariate Cox regression models and hazard ratios (HR) were used to examine first time post-injury CVD admissions. Results: The burn cohort had a higher rate of CVD (combined) admissions (IRR, 95%CI: 1.16: 1.08-1.24) and spent longer in hospital (IRR, 95%CI: 1.37, 1.13-1.66) than the non-burn trauma cohort. Both the burn cohort (IRR, 95%CI: 1.50, 1.40-1.60) and the non-burn trauma cohort (IRR, 95%CI: 1.29, 1.21-1.37) had higher adjusted rates of post-injury CVD admissions compared with the non-injured cohort. The burn cohort (HR, 95%CI: 2.27, 1.70-3.02) and non-burn trauma cohort (HR, 95%CI: 2.19, 1.66-2.87) experienced significantly elevated first time CVD admissions during the first 6 months after injury, decreasing in magnitude from 6 months to 5 years after injury (HR, 95%CI: burn vs. non-injured; 1.31, 1.16-1.48; non-burn trauma vs. non-injured; 1.16, 1.03-1.31); no significant difference in incident admission rates was found beyond 5 years (HR, 95%CI: burn vs. non-injured; 0.99, 0.92-1.07; non-burn trauma vs. non-injured; 1.00, 0.93-1.07). Conclusions: Burn and non-burn trauma patients experience elevated rates of post-injury CVD admissions for a prolonged period after the initial injury and are particularly at increased risk of incident CVD admissions during the first 5-years after the injury event. Detailed clinical data are required to help understand the underlying pathogenic pathways triggered by burn and non-burn trauma. This study identified treatment needs for injury patients, burn and non-burn, for a prolonged period after discharge.